Eco-innovative technology for wastewater treatment and reuse in MENA region: case of Lebanon - El Moll, Ahmad (Frontiers in Sustainability, 2023)
Water scarcity is a significant problem worldwide especially in Middle East and North Africa, to which the reuse of wastewater after appropriate treatment could offer a sustainable solution. With recent advances in wastewater treatment technologies and reuse, it is possible to obtain wastewater effluent of consistently high quality, which can then be reused in the agricultural sector. Thus, facing of water shortage, deficiency of sanitation and pollution by wastewater in the Mediterranean region, the decentralization using eco-innovative technology, focuses mainly on the wastewater treatment on-site and on the local recycling and reuse of resources contained in domestic wastewater, represents a real and well solution. Therefore, sustainable solutions for wastewater management will be discussed, with a focus on the role of innovative technology with detailed description of the wastewater treatment process. Additionally, the implications of wastewater reuse in agriculture sector in the context of the circular economy as potential solutions will also be presented in this paper.